Implementasi Program Corporate Social Responsibility PT UPC Sidrap Bayu Energi dalam Meningkatkan Kesejahteraan Masyarakat - Sulvinajayanti, Sulvinajayanti; Ramli; Abd. Halim, K; Bahfiarti, Tuti; Sultan, M. Iqbal (KURIOSITAS: Media Komunikasi Sosial Keagamaan, 2024)
PT UPC Sidrap Bayu Energi realises that, in the long term, its existence must not only produce electricity but also be able to provide benefits to the surrounding community. This study looks at how planning and implementing CSR programs has an impact on improving community welfare. This research uses a qualitative descriptive approach and focuses on CSR programs' planning and implementation processes. The research results show that the first stage in planning a CSR program is assessing the community's environmental, social, and economic needs. CSR plans by respecting local culture, cultural heritage, and community rights. The company committee, CSR employees, local government, Sidrap District CSR Forum, and community leaders were involved in the planning. Every December, a program planning mechanism is carried out with a meeting between local governments to find government work programs that can be combined with CSR programs. Implementing CSR programs and providing benefits to the company must obtain approval and support from the company's top management. This ensures that program implementation is fully supported by the company's resources, including financial resources, namely the budget allocated for program implementation, and human resources, namely the employees employed by the company.